Dimensional Accuracy of Dental Casting Patterns Fabricated Using Consumer 3D Printers - Ishida Yoshiki; Miura Daisuke; Miyasaka Taira; Shinya Akikazu (MDPI, 2022)
Consumer 3D printers have improved considerably due to the evolution of additive manufacturing. This study aimed to examine the accuracy of consumer printers in dental restoration. Cylindrical patterns mimicking a full crown were created and enlarged from 100% to 105% of the original size. Two types of consumer 3D printers, including a fused deposition modeling (FDM) device and a stereolithography (SLA) device, and two types of dental 3D printers, including a multi-jet device and an SLA device, were used to fabricate the patterns. Then, the outer and inner diameters and depths, and surface roughness of the patterns were measured. The changing rates of the outer diameter of models created using dental printers were significantly smaller than those of the models created using consumer printers (p < 0.05). Significantly greater surface roughness was obtained in the tooth axis of the model fabricated using the consumer FDM device (p < 0.05). However, no significant differences were observed on the surface roughness of both axes between the consumer SLA device and the dental devices (p > 0.05). However, FDM showed larger surface roughness than dental devices in both axes (p < 0.05). Thus, the SLA consumer printer can be applied to fabricate resin patterns with enlargement editing of 1-3% along the horizontal axis.